Thallus variation of Sargassum polycystum from Central Java, Indonesia - DWI SUNU WIDYARTINI; PUDJI WIDODO; A.B. SUSANTO (Biodiversitas Journal of Biological Diversity, 2017)
Widyartini DS, Widodo P, Susanto AB. 2017. Thallus variation of Sargassum polycystum from Central Java, Indonesia. Biodiversitas 18: 1004-1011. Sargassum polycystum C. Agardh has characteristic of highly polymorphic thalli among individuals in its population. The shape and size of thalli are variable among the individuals. The study was aimed at knowing the variation of S. polycystum thalli grown in different beaches of Central Java. The data showed that the thalli of the S. polycystum grown in the Karimunjawa had more variation than those grown in the Menganti Beach, as obviously seen on its leaves and vesicles. There was a relationship between salinity and pH of the Menganti Beach of the length of vesicle S. polycystum, but nitrate and phosphate content weren't correlated of variation thalli. Temperature, salinity, and pH of Karimunjawa Beach were correlated with the vesicle's color, nitrate and phosphate correlated of the width as well as upper and lower surfaces of the leaves, phosphate also correlated with the leaf edge and vesicle diameter. Environmental factors in the Menganti Beach had not significantly affected the thalli variation, but salinity and pH had an effect on vesicle length. Temperature, salinity, and pH in the Karimunjawa Beach significantly affected the vesicle color, nitrate and phosphate affect the width of leaves as well as their upper and lower surface. Phosphate also affected the edge of the leaf and the vesicle diameter